Comparison of the Differences in Survival Rates between the 7th and 8th Editions of the AJCC TNM Staging System for Gastric Adenocarcinoma: a Single-Institution Study of 5,507 Patients in Korea - Kim, Sung Geun; Seo, Ho Seok; Lee, Han Hong; Song, Kyo Yong; Park, Cho Hyun (Journal of gastric cancer, 2017)
The aims of this study were to compare the 7th and 8th editions of the American Joint Committee on Cancer (AJCC) staging manuals on tumor, node, and metastasis (TNM) staging systems and to evaluate whether the 8th edition represents a better refinement of the 7th staging system, when applied for the classification of gastric cancers. A total of 5,507 gastric cancer patients, who underwent treatment from January 1989 to December 2013 at a single institute, were included. We compared patient survival rates across the disease groups classified according to the 7th and 8th editions of the AJCC TNM staging systems. Stage migration was observed in 6.4% (n=355) of the patients. Of these, 3.5% (n=192) and 2.9% (n=158) of patients showed a higher stage and lower stage, respectively. According to the 8th edition of the AJCC TNM staging criteria, the 5-year overall survival rates of the patients with stage IIIB and IIIC showed a significant difference (40.8% vs. 20.2%, P<0.001) whereas no significant differences in the 5-year overall survival rates were observed according to the 7th edition criteria (37.6% vs. 33.2%, P=0.381). Restaging stage III cancers according to the 8th edition of the AJCC TNM classification criteria improved survival rate discrimination, particularly, in institutes where the stage III patients were not distinctly categorized.